Implementation of Complete Systematic Land Registration (PTSL) as an Effort to Accelerate Land Certification in Banyumas Regency: Constraints and Challenges - Tarisa Indriyani; Muslih Faozanudin; Tobirin Tobirin (Journal of Public Policy, Governance and Local Government, 2026)
The increasing public demand for legal certainty over land and quality public services has driven the importance of the Complete Systematic Land Registration Program (PTSL) as a form of public service in the land sector. The implementation of PTSL in Banyumas Regency involves various stakeholders, from the Land Office, village/sub-district apparatus teams, to the community, utilizing digitalization (e- PTSL, GIS) to increase transparency, accountability, and efficiency. This study aims to analyze the implementation of PTSL using the Van Meter & Van Horn framework and assess the program's success through the Asian Development Bank (ADB) principles of Transparency, Accountability, Predictability, and Participation. The study used a qualitative approach with observation, interviews, and documentation methods. The results show that the standards and objectives of the PTSL policy have been clearly defined, resources and technology support implementation, and communication between stakeholders is quite good. However, obstacles such as limited human resources, uneven community participation, limited field supervision, and land ownership conflicts still occur. Analysis of the ADB principles shows that the success of PTSL is influenced by active community participation, administrative digitalization, and coordination between stakeholders, while obstacles hamper the effectiveness of program implementation. Overall, the study concluded that the PTSL implementation has been quite effective, but ongoing improvements in community engagement and field supervision are needed to optimize the program's success.